Utilization of IFF's flavorfit low calorie sweeteners in the development of sugar-reduced ready-to-drink and aspartame-free powdered soft drink beverages - Pabustan, Ruth Ivane T.
Reducing the sugar content of sugar-sweetened beverages has been claimed to be one of the most efficient strategies for decreasing sugar intake. However, different non-nutritive sweeteners (especially the artificial ones) available in the market which may replace sucrose in beverages may not be that acceptable to consumers. The present work aimed to produce a sugar-reduced ready to drink beverages with the use of different combinations of the International Flavors and Fragrances Inc.'s (IFF) FlavorFit low calorie sweeteners with sugar-like characteristics; develop acceptable aspartame-free powdered soft drink beverages using optimal formulations of IFF's FlavorFit low calorie sweetener and; determine the consumer acceptability of the developed beverages. Twenty five artificial and natural non-nutritive sweeteners were shortlisted into five artificial and five natural IFF FlavorFit low calorie sweeteners using Descriptive Analyis (Flavor Profile Method). Lemon iced tea was formulated with different amounts of added sugar (6º, 4º and 0ºBrix) in comparison with the control (11ºBrix). Samples were subjected to consumer acceptance test and results showed that overall, 0 Art F and 4 Nat F and 4 Art A were significantly different with the control. This results imply that 4 Art D, 6 Nat A, 4 Art B and 6 Nat B can be released to the market as they are comparable with sucrose. On the other hand, the development of aspartame-free beverage was done by replacing aspartame- acesulfame potassium content of the control with different IFF FlavorFit low calorie sweetener blends. Aspartame-free orange solutions A, C, E, F and H were accepted by the panel. All accepted solutions do not contain traces of bitterness and off flavors.